What attributes characterize the beneficiary households after three years of implementation of National Food Security Act?. (5th August 2021) - Kumar, Amit; Suar, Damodar; Sahoo, Bimal Kishore
Abstract : This study examines the factors associated with food security after three years of implementation of the National Food Security Act, 2013. Fifteen hundred and fourteen households in three states of India—563 from Bihar, 557 from Uttar Pradesh, and 394 from Haryana—were surveyed. Data on beneficiary status, calorie consumption, economic status, social status, health status, and women empowerment were analyzed using binary logistic regression. Findings suggest that beneficiary had more employment in families, normal and deficit calorie intake, used cow dung cake as fuel, more children enrolment in primary and secondary schools, and adoption of family planning measures. These improvements have occurred after three years of implementation of the Act, and through supply of food grains to poor families.